1995
DOI: 10.4049/jimmunol.154.7.3156
|View full text |Cite
|
Sign up to set email alerts
|

Novel in vitro model for high-rate IgA class switching.

Abstract: The parameters necessary for induction of high-rate IgA class switching are unknown. Thus, although TGF-beta is switch factor for the IgA class, the percentage of membrane (m)IgA+ cells generated in vitro in response to TGF-beta and various individual modes of B cell activation is limited to 1 to 2% of the total B cell population, a percentage far below that observed within Peyer's patches. In this report we determined a set of parameters that act synergistically to generate up to 15 to 20% mIgA+ cells in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Surprisingly, both the G/C and hotspot targeting are much higher in GL 5′Sμ segments amplified from cells induced with LPS + IL‐4 than with LPS ± anti‐δ dextran (Tables II and III). It is known that IL‐4 treatment can increase CSR without increasing GL transcript levels (Shockett and Stavnezer, 1991; McIntyre et al ., 1995). Perhaps IL‐4 increases the size of the region targeted by AID, resulting in introduction of mutations at G/C base pairs and hotspots over a greater region, although the frequency of mutation in the GL 5′Sμ region was not increased in cells treated with LPS + IL‐4 (Table I, row 6).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, both the G/C and hotspot targeting are much higher in GL 5′Sμ segments amplified from cells induced with LPS + IL‐4 than with LPS ± anti‐δ dextran (Tables II and III). It is known that IL‐4 treatment can increase CSR without increasing GL transcript levels (Shockett and Stavnezer, 1991; McIntyre et al ., 1995). Perhaps IL‐4 increases the size of the region targeted by AID, resulting in introduction of mutations at G/C base pairs and hotspots over a greater region, although the frequency of mutation in the GL 5′Sμ region was not increased in cells treated with LPS + IL‐4 (Table I, row 6).…”
Section: Discussionmentioning
confidence: 99%
“…When exogenous cytokines including IL-2 and IL-10 or IL-10 and TGF-β are additionally treated, induction of differential regulation of IgG1 and IgG3 was observed. Other studies also revealed that mitogen [ 72 ] and virulent factors including Staphylococcus aureus Cowan and lipopolysaccharide [ 66 , 67 , 73 75 ] can be promising stimulant factors for in vitro IgA production in human PBMC or B cell line [ 75 ]. Table 2 shows the IgA CSR factors and their working mechanism inducing IgA CSR in B cells.…”
Section: Modeling Iga Production In Vitromentioning
confidence: 99%
“…B , C high-rate IgA class switching of B cells obtained from spleen induced by dual combinations of the multivalent antigen receptor crosslinker, aδ-dex, CD40L, and/or LPS, plus IL-4 + IL-5, in the presence or absence of TGF-β. The percentages of membrane IgA positive (mIgA + ) cells were analyzed using flow cytometry [ 67 ] …”
Section: Modeling Iga Production In Vitromentioning
confidence: 99%
“…It was reported to decrease proliferation of B cells and to increase apoptosis of immature or resting B cells in mice and humans (160)(161)(162)(163). Furthermore, TGF-b can inhibit immunoglobulin synthesis and class switching in IgG isotypes and promotes the production of IgA in mice and humans (164)(165)(166).…”
Section: B Cellsmentioning
confidence: 99%